IMPLEMENTATION OF E-GOVERNMENT IN VILLAGE ASSET MANAGEMENT THROUGH THE VILLAGE ASSET MANAGEMENT SYSTEM (SIPADES) IN SUMOKALI VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY - Rachmawan, Mochammad Arif; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to describe and analyze the implementation of e-government in village asset management through the Village Asset Management System (SIPADES) application in Sumokali Village, Candi District, Sidoarjo Regency.  The main objective of this study is to evaluate the extent to which the SIPADES application supports effectiveness, efficiency, and transparency in village asset management. Method: This study uses a qualitative method with a descriptive approach. Data is collected through interviews, observations, and documentation from relevant parties, as well as the collection of supporting documents. Results: The results of the study show that in the organizational aspect, the organizational structure in the village has been formed but human resources are still limited. In terms of interpretation, operators' understanding of the application is still low due to the lack of socialization from related agencies. Meanwhile, in the application aspect, even though the initial SOPs and training are available, the implementation of the SIPADES application still faces technical obstacles such as system disruptions and errors during working hours, which cause operators to have to work outside of working hours. Novelty: This research makes a new contribution by revealing the specifics of the obstacles to the implementation of SIPADES at the village level through the implementation theory approach of Charles O. Jones. Focusing on the local context of Sumokali Village provides a real picture of the challenges and opportunities in the implementation of application-based e-government in rural areas.